Medication Adherence in Patients with Chronic Disease at Primary Health Center in Yogyakarta - Salma Fajar Puspita; Indah Erlinda; Dwi Tamara Imelda; Muslimatul Khotimah; Vitarani Dwi Ananda Ningrum (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Adhering to medication in chronic diseases like hypertension and diabetes mellitus can prevent complications and reduce hospitalizations. Primary Health Center (PHC), leads in managing patients with chronic diseases who are expected to comply with medication. This study aims to analyze the medication adherence level among patients with chronic diseases and its influencing factors. The research employed a cross-sectional design with a purposive sampling technique at a PHC in Bantul Regency, Yogyakarta. Data on the demographic and clinical characteristics of patients were collected from medical records. Meanwhile, the assessment of medication adherence used pill-count method and MMAS-8. Patients were categorized as adhering to the medication if the MMAS-8 score was 8 and ≥80% for the pill-count method. A total of 210 patients with the therapeutic dosage drug regimen for controlling chronic disease were included. The adherence rate among patients measured with MMAS-8 was primarily classified as low (72.86%). However, the pill-count method showed a compliance rate of over 90%. Based on MMAS-8, disease duration (0.022), caretaker (0.000), comorbidities (0.015), and number of medications (0.049) affected the adherence level in the elderly. However, only a gender was found in adults (0.032). Over half of chronically ill patients in PHC were found to have low adherence rates when assessed using MMAS-8. The contradictory medication adherence levels between the two tools require further studies to confirm the best approach in measuring adherence in the community setting. An effective, interactive, and collaborative approach by healthcare providers is needed to improve medication adherence.